Practical financial statement analysis - Foulke, Roy Anderson (New York : McGraw-Hill, 1961)
In this edition, applicable material in the Accounting Research Bulletins of the American Institute of Certified Public Accountants issued since the fourth edition of this volume was published in 1957 has been included in proper chapters. Accounting terminology and phraseology, which is in constant evolution, has been brought up to minute. The guide to the classification of balance sheet items in Chapter 4 has been materially expanded also.
Includes bibliographical references and index.
ne 18/10/2018
Loans
Keywords: Financial statements; Corporations